2021
DOI: 10.1038/s41467-021-23889-0
|View full text |Cite
|
Sign up to set email alerts
|

A synthetic circuit for buffering gene dosage variation between individual mammalian cells

Abstract: Precise control of gene expression is critical for biological research and biotechnology. However, transient plasmid transfections in mammalian cells produce a wide distribution of copy numbers per cell, and consequently, high expression heterogeneity. Here, we report plasmid-based synthetic circuits – Equalizers – that buffer copy-number variation at the single-cell level. Equalizers couple a transcriptional negative feedback loop with post-transcriptional incoherent feedforward control. Computational modelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 68 publications
1
17
0
Order By: Relevance
“…Plasmid buffering in such systems allows for copy number adjustment in response to different growth environments. A recent study by Yang et al created a synthetic circuit for eliminating gene dosage variation in individual mammalian cells 24 . Their method buffers plasmid CN variability in mammalian cells to reduce heterogeneity while we use plasmid CN flexibility to buffer circuit burden.…”
Section: Discussionmentioning
confidence: 99%
“…Plasmid buffering in such systems allows for copy number adjustment in response to different growth environments. A recent study by Yang et al created a synthetic circuit for eliminating gene dosage variation in individual mammalian cells 24 . Their method buffers plasmid CN variability in mammalian cells to reduce heterogeneity while we use plasmid CN flexibility to buffer circuit burden.…”
Section: Discussionmentioning
confidence: 99%
“…As an example of the latter, a recent study demonstrated a five-fold noise reduction by incorporating negative feedback regulation gene circuits (i.e., TetR repressor fused with a Tet-inhibiting peptide; Guinn and Balázsi, 2019 ). Such synthetic circuits can also be multiplexed orthogonally to probe multigene expressions in contribution of cell phenotypes (Szenk et al, 2020 ) and buffering gene dosage variation across cell populations for a more homogeneous gene expression control (Yang et al, 2021 ).…”
Section: Optogenetics In Genome Modification and Regulationmentioning
confidence: 99%
“…Studies in the field of biosynthetic gene cluster expression 19 and microbial community engineering 20 have shown that similarities in phylogeny and genotypic profiles can accurately predict metabolic phenotype, which suggests genome relatedness could be a potential predictor of genetic circuit performance. On the other hand, the functional phenotype of expression plasmids and genetic devices has been shown to be coupled to physiological metrics such as growth rate 21, 22 , gene copy number 23, 24 , codon usage bias 25, 26 and growth burden 27, 28 in a number of studies. These studies have however, only considered a single or select combination of physiology metrics as explanatory variables of phenotype within a single model chassis.…”
Section: Introductionmentioning
confidence: 99%